1995
DOI: 10.1111/j.1365-2125.1995.tb04407.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐effect relationship of levodopa in patients with Parkinson's disease after oral administration of an immediate release and a controlled release formulation.

Abstract: 1 The relationship between plasma concentration of levodopa and motor-response was investigated in 12 patients with Parkinson's disease who showed marked response fluctutations, after a single oral dose of an immediate release (IR) formulation (100 mg levodopa/25 mg benserazide) and a controlled release (CR) formulation (300 mg levodopa/75 mg benserazide), using a double-blind, randomized, cross-over design. 2 The sum score of the Columbia University Rating Scale (CURSE) was used for pharmacodynamic assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
(26 reference statements)
0
17
0
1
Order By: Relevance
“…Maximum levodopa concentrations, however, were attained quicker in the presence than in the absence of food with mean t max values of 1.3 and 2.5 h, respectively. A shorter delay to turn to the ON-state would therefore be expected when patients take Madopar ® DR in close association with a meal [2]. However, the results of a pilot study with Madopar ® DR in 61 patients with Parkinson's disease suggested that efficacy and tolerability were not influenced by the interval between drug and meal intake [15].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Maximum levodopa concentrations, however, were attained quicker in the presence than in the absence of food with mean t max values of 1.3 and 2.5 h, respectively. A shorter delay to turn to the ON-state would therefore be expected when patients take Madopar ® DR in close association with a meal [2]. However, the results of a pilot study with Madopar ® DR in 61 patients with Parkinson's disease suggested that efficacy and tolerability were not influenced by the interval between drug and meal intake [15].…”
Section: Discussionmentioning
confidence: 77%
“…Although complex in advanced stages of the disease, relationships exist between plasma levels of levodopa and clinical efficacy in patients with Parkinson's disease [2]. Immediate-release formulations of levodopa suffer from high peak levels and a short elimination half-life of only about 1 h, resulting in the need of frequent dosing [3].…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium half time T eq was derived by ln (2)/k e0 and could be interpreted as a measure for the lag time between changes of drug concentration in the central compartment and changes of the drug effect. [12][13][14] Most published studies on the concentration-effect relationship of levodopa were carried out in patients with fluctuating idiopathic PD and focused on improvement of motor impairment (rigor, tremor, and akinesia) by levodopa. 12,13,15 Despite some heterogeneity in regard to the study designs (that is, different score systems for the motor response), these studies showed almost consistent findings and proved the E max model to be the most suitable to describe the concentration-effect relationship of levodopa.…”
Section: Evaluation Of the Datamentioning
confidence: 99%
“…[12][13][14] Most published studies on the concentration-effect relationship of levodopa were carried out in patients with fluctuating idiopathic PD and focused on improvement of motor impairment (rigor, tremor, and akinesia) by levodopa. 12,13,15 Despite some heterogeneity in regard to the study designs (that is, different score systems for the motor response), these studies showed almost consistent findings and proved the E max model to be the most suitable to describe the concentration-effect relationship of levodopa. In all studies, the steepness of the concentration-effect curves, characterized by the Hill coefficient N, was high (>5 units), indicating an almost immediate onset of motor response to levodopa when the EC 50 is reached and the appearance of off reactions when concentrations are below this level.…”
Section: Evaluation Of the Datamentioning
confidence: 99%
“…Motor fluctuations are at least partially caused by the extreme fluctuations in levodopa plasma concentrations (Fahn, 1974;Sweet et al, 1974;Tolesa et al, 1975;Eriksson et al, 1984;Nutt et al, 1984;Poewe et al, 1986;Nutt, 1987;Mouradian and Chase, 1988;Mouradian et al, 1988a). In order to achieve constant plasma levels of levodopa this sustained-release (SR) formulations have been developed and applicated in recent years (Poewe et al, 1986;Kleedorfer and Poewe, 1992;Kurth et al, 1993;Pahwa et al, 1993;Stocchi et al, 1994;Bergemann et al, 1994;Harder et al, 1995). Beneficial effects of levodopa "slow release" treatment mainly in patients with "wearing off" fluctuations were observed, but duration of interdose dyskinesia increased.…”
Section: Introductionmentioning
confidence: 97%